ASSISTANCE IN IMPROVING EDUCATION AND DEVELOPMENT OF PARAMADINA TK-PAUD - Hosna, Rofiatul; Mukit, Abdul; Idawati, Khoirotul; Hanifudin, Hanifudin (PT Altin Riset Publishing, 2025)
The purpose of this assistance is to ensure that the potential of early childhood in Sidokerto Village develops normally and optimally, supported by educators with strong professional, social, and personal competencies. Principles of Learning: These principles are guidelines that children must follow during learning. Children are active learners. As they move, they seek stimulation to enhance their learning opportunities. Children use their entire bodies as tools for learning and energetically search for ways to achieve their maximum potential. Child Learning and Maturity: Learning is influenced by a child's maturity. Teachers must understand the developmental stages children can achieve and what needs to be done to facilitate such maturity. Children learn through a combination of physical, social, and reflective environments. Through these experiences, children acquire knowledge. It is the teacher's responsibility to provide an environment that enables children to gain physical and social experiences and reflect on them. Children learn in different styles visual, auditory, and kinesthetic, and through play. Through play, children can understand, create, manipulate symbols, and transform objects. Collaboration Among Educational Tri-Centers: Cooperation among parents, schools, and the community is essential to nurture the full potential of children, enabling them to develop optimally and creatively according to their competencies.